2004
DOI: 10.5483/bmbrep.2004.37.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nucleotide Sequence of a Polyubiquitin Gene (PUBC1) from Arabian Camel, Camelus dromedarius

Abstract: Molecular amplification and sequencing of genomic DNA that encodes camel polyubiquitin (PUBC1) was performed by a polymerase chain reaction (PCR) using various sets of primers. The amplification generated a number of DNA fragments, which were sequenced and compared with the polyubiquitin coding sequences of various species. One DNA fragment that conformed to 325 bp was found to be 95 and 88% homologous to the sequences of human polyubiquitin B and C, respectively. The DNA translated into 108 amino acids that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The final discussed protein is UBBP4 ( ENSP00000464265 ), which has been widely reported to act as a pseudogene and is functionally correlated with psoriasis [ 51 , 52 ]. Similar to UBL4A and UBL4B, UBBP4 can contribute to the regulation of the ERAD pathway [ 53 ] and therefore may be functionally correlated with COVID-19 infection. This relationship validates the efficacy and accuracy of our prediction.…”
Section: Resultsmentioning
confidence: 99%
“…The final discussed protein is UBBP4 ( ENSP00000464265 ), which has been widely reported to act as a pseudogene and is functionally correlated with psoriasis [ 51 , 52 ]. Similar to UBL4A and UBL4B, UBBP4 can contribute to the regulation of the ERAD pathway [ 53 ] and therefore may be functionally correlated with COVID-19 infection. This relationship validates the efficacy and accuracy of our prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Another South American Camelid study, which validated the use of control region of mitochondrial genome as a molecular biomarker to deduce data on Camelid genetic relationships and population biodiversity (Mate et al, 2004). Similarly, nucleotide sequence of a polyubiquitin gene (PUBC1) of (Camelus dromedarius) was also used to have an insight of genetic diversity in one of the Arabian camel study, which revealed that there are genetic variation, one of the 325 bp motif was 95 and 88% identical to human polyubiquitin genes B and C respectively and synonymous mutations were observed, while their amino acid sequence was 100% homologous (Al-Khedhairy, 2004). Microsatellite markers can also be served as a tool for determining population diversity, one of the Egyptian studies revealed that RAPD markers results showed genetic variation between and within different camel breeds.…”
Section: Discussionmentioning
confidence: 99%
“…This camel is found in the Arabian deserts and arid and semiarid areas of the Middle East (Thomas et al, 1985;Hussein et al, 1992;Al-Khedhairy, 2004). The Arabian camel has unique physiological modifications and is able to live in harsh desert conditions, such as high temperature, direct exposure to sunlight and lack of water resources, with this animal being able to survive without drinking water for weeks (Hussein et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA sequence of camels exhibits wide variations with other species, including human; however, functional similarities exist. Therefore, studies of camel protein represent a potentially viable target for human applications (Al-Khedhairy, 2004).…”
Section: Introductionmentioning
confidence: 99%